Contribution of ICT in the cultural heritage management in Cyprus and Eastern Mediterranean: How Unesco Chair in Cyprus University of Technology can blend ICT and Space Technologies in the benefit of the community - Ioannides, Marinos; Hadjimitsis, Diofantos G.; Themistocleous, Kyriacos (My University, 2018)
The EU H2020 INCEPTION (G.A.665220) project is expected to solve the shortcomings of state-of-the-art 3D reconstruction by significantly enhancing the functionalities, capabilities and cost-effectiveness of instruments and deployment procedures for 3D laser survey, data acquisition and processing. Indeed, the integration of several geospatial techniques such as GIS, GPS, remote sensing can assist the assessment of the accuracy and efficiency of 3D capturing both through hardware interfaces as well as software algorithms. INCEPTION methods and tools will result in 3D models that are easily accessible for all user groups and interoperable for use by different hardware and software. It develops an open-standard Semantic Web platform for Building Information Models for Cultural Heritage (HBIM) to be implemented in user-friendly Augmented Reality (VR and AR) operable on mobile devices. This paper explores the opportunities from a closed collaboration between the Digital Heritage Research lab and the Eratosthenes Research Centre within the School of Engineering and Technology at the Cyprus University of Technology in the integration of such geospatial tools in the creation of 3D models for cultural heritage management for risk assessment purposes in UNESCO sites within urban and rural environments in Cyprus.
Keywords: 3D reconstruction; 3D Models